Antimicrobial resistance of Salmonella Typhi isolated in the State of Pará, Brazil - Oliveira Souza, Cintya de (2010)
Antimicrobial resistance has been widely studied in every bacterial genus, especially among those agents responsible for epidemic diseases, such as typhoid fever. Outbreaks have lead to increased usage and erroneous administration of antimicrobial drugs, contributing to the emergence of resistant bacterial strains. Therefore, this study evaluated the resistance of 44 strains of Salmonella Typhi to the main antibiotics used in the treatment of typhoid fever. Of the 44 strains isolated from 2003 to 2005, ten (2.7%) were resistant to at least one microbial drug. Among the ten resistant Salmonella Typhi strains, nine showed monoresistance to nitrofurantoin or tetracycline. Only one case of concomitant resistance to two drugs (chloramphenicol and nitrofurantoin) was observed, in 2005. The Northern Region of Brazil is considered an endemic area for typhoid fever and has shown growing drug resistance in the three years studied. Thus, we must continue to monitor the resistance of Salmonella Typhi to antimicrobial drugs, especially chloramphenicol, to ensure that it remains the drug of choice for the treatment of typhoid fever in the Region, as it is inexpensive and the disease responds well to it.